TOMM34 serves as a candidate therapeutic target associated with immune cell infiltration in colon cancer - Li, Zhigui; Yang, Hongzhao; Liu, Jianbo; Li, Li; Wang, Xiaodong (Frontiers in Oncology, 2023)
Background: Colon cancer represents one of the most pervasive digestive malignancies worldwide. Translocase of the outer mitochondrial membrane 34 (TOMM34) is considered an oncogene and is implicated in tumor proliferation. However, the correlation between TOMM34 and immune cell infiltration in colon cancer has not been investigated. Materials and methods: Based on multiple open online databases, we performed integrated bioinformatics analysis of TOMM34 to evaluate the prognostic value of TOMM34 and its correlation with immune cell infiltration. Results: TOMM34 gene and protein expression levels were elevated in tumor tissues compared with normal tissues. Survival analysis revealed that upregulation of TOMM34 was significantly associated with poorer survival time in colon cancer. High TOMM34 expression was dramatically related to low levels of B cells, CD8+ T cells, neutrophils, dendritic cells, PD-1, PD-L1 and CTLA-4. Conclusions: Our results confirmed that high expression of TOMM34 in tumor tissue correlates with immune cell infiltration and worse prognosis in colon cancer patients. TOMM34 may serve as a potential prognostic biomarker for colon cancer diagnosis and prognosis prediction.